Determine exogenous human DDAH2 gene function in rabbit bone marrow–derived endothelial progenitor cells in vitro. (1st February 2017) - Shoeibi, Sara; Mohammadi, Shabnam; Sadeghnia, Hamid Reza; Mahdipour, Elahe; Ghayour‐Mobarhan, Majid
Abstract : The in vitro amplification of endothelial progenitor cells (EPCs) is an important method because of its role in gene transferring and regenerative medicine. In this study, we isolated rabbit bone marrow–derived EPCs to further manipulation and overexpression of dimethylarginine dimethylaminohydrolase ( DDAH ) in EPCs. Isolated EPCs were cultured, expanded in endothelial basal medium. Morphology of EPCs and expression levels of surface markers detected using immunocytochemistry staining and through the use of flow cytometery. Endothelial progenitor cells were transfected with plasmid vectors expressing human DDAH2 ( DDAH2 ‐EPCs). Three days after gene transfer, positive transfected‐EPCs proliferation and DDAH activity were assayed. We observed colonies conformation and endothelium‐like morphology gradually in the third week of culture. Characterization results revealed positive expression of EPC surface markers CD106, Flk‐1, vWF, and CD34 using few identification techniques. Overexpression of DDAH2 increased citrulline production after 96 hours of transfection, 235.34 ± 0.69 vs 95.26 ± 5.76 ng/mL; P  = .023. These results suggest that cell population with EPC characteristics can be simply isolated from rabbit bone marrow and successfully engineered to overexpress exogenous gene. In this study, we offer a feasible method to isolate and identify EPCs from bone marrow. In addition, an efficient transfection with a plasmid vector (without risk of interference) can be constructed a hybrid structure with EPC and DDAH2 gene to examine their function in vitro.